1997
DOI: 10.1038/sj.bmt.1701000
|View full text |Cite
|
Sign up to set email alerts
|

High-dose chemotherapy with autologous peripheral blood progenitor cell support for primary breast cancer in patients with 4–9 involved axillary lymph nodes

Abstract: Summary:different from that measured in historical controls who received 600 mg/m 2 of BCNU. Combined hospital and physician charges for patients treated at the University Breast cancer patients with more than three involved axillary lymph have a high likelihood of relapse after of Colorado decreased from a mean of $125 845 for the first four patients to $77 126 for the final seven patients. adjuvant therapy. Early results of administration of high-dose chemotherapy (HDCT) and autologous periWe conclude that H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0

Year Published

1999
1999
2007
2007

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(19 citation statements)
references
References 3 publications
(3 reference statements)
2
17
0
Order By: Relevance
“…This is significant, because many current clinical studies indicate that threefold accelerated dosing of doxorubicin is more effective in treating node-positive breast cancers (Bearman et al, 1997). However, doxorubicin has associated cardiotoxicity and there is a significant morbidity associated with accelerated dosing regimens.…”
Section: Discussionmentioning
confidence: 93%
“…This is significant, because many current clinical studies indicate that threefold accelerated dosing of doxorubicin is more effective in treating node-positive breast cancers (Bearman et al, 1997). However, doxorubicin has associated cardiotoxicity and there is a significant morbidity associated with accelerated dosing regimens.…”
Section: Discussionmentioning
confidence: 93%
“…[14][15][16][17][18] Many phase 2 trials have shown the potential therapeutic efficacy of high-dose chemotherapy in autologous PBPC transplantation for high-risk stage II/III breast cancer. [5][6][7][8][9][10] 'High-risk' is generally defined as у10 involved axillary nodes, although data exist showing efficacy of PBPC transplantation in women with 4-9 axillary nodes involved. However, among these many reports, only one describes a multivariate analysis of prognostic factors influencing survival.…”
Section: Discussionmentioning
confidence: 99%
“…Data from these phase II trials suggested that 60-70% chance of patients with high-risk stage II/III breast cancer might be rendered disease-free with autologous transplantation. [5][6][7][8][9][10] Preliminary results, however, of prospective randomized trials comparing autologous transplantation to less intensive chemotherapy have not shown a significant difference in overall survival at the time of data analysis. 11,12 One trial did show that transplantation was associated with a decreased relapse rate; however, this had not translated into improved survival at the time of data analysis.…”
mentioning
confidence: 99%
“…We retrospectively analysed tumour samples from patients who were prospectively enrolled in phase II and III trials of HDC for HRPBC at the University of Colorado between 1990 and 2001. A total of 234 patients were accrued in these studies, which were open to patients with 4 -9 positive axillary nodes (n ¼ 102) (Bearman et al, 1997;Moore et al, 2007) and 10 or greater positive nodes (n ¼ 132) (Nieto et al, 2004;Peters et al, 2005). Those trials, as well as the current retrospective review of tumour blocks, were approved by the Cancer Center Protocol Review Committee and the Institutional Review Board.…”
Section: Patient Populationmentioning
confidence: 99%